Petrographical study of ewekoro carbonate rocks, in ibese, south western nigeria (2010)
Limestone deposits can be found in every system of the geologic column since the Precambrian. In classifying this rock, various attempts have been made and notable among them is the classification scheme based on three components: allochems, cements and matrix. Another classification divided limestoneonthe basis of texture into grainstone, packstone, mudstone, wackestone and boundstone. Texturally, limestone ranges from fine to coarse grained with aragonite and calcite as the most common minerals. This work was aimed at identifying and describing both the allochemical and orthochemical components of the limestone deposits in order to classify and deduce their depositional environment.Eight core samples of limestone deposits representing the Ewekoro Formation of the Dahomey Basin were studied petrographically.The result of the analysis carried out on the samples showed that the Ibese limestone is composed of the following allochems: sponges, echinoids, bivalves, coralline algae, and pelecypod which represent the skeletal content and intraclasts, pellets and ooids which represent the non skeletal grains. The orthochemical constituents include the carbonate mud matrix and the sparry calcite cement.These constituents observed from the slides indicate that the Ibese limestone belongs to the class of wackestone and could have been deposited in a quiet and low energy environment.